Kilka uwag o japońskim przekładzie Pieśni o zamordowanym żydowskim narodzie Jicchoka Kacenelsona (Między Oryginałem a Przekładem, 2022)
SOME REMARKS ON THE JAPANESE TRANSLATION OF THE SONG OF THE MURDERED JEWISH PEOPLE BY YITSKHOK KATSENELSONThe aim of the text is to present the Japanese translation of Yitskhok Katsenelson’s Song of the murdered Jewish people, authored by two Germanists, Masatomo Asukai and Kazuyuki Hosomi, published in 1999 under the title Horobosareta Yudaya no tami no uta by the Tokyo publishing house Misuzu. In addition to providing details of the publication itself, as well as the profiles of the translators and the background to the creation of the Japanese edition, the linguistic aspect of the translation is discussed in particular, focusing on problems of versification, the syntactic devices used and the choice of vocabulary. The article provides a more detailed analysis of selected, albeit representative, fragments of the translation, as varied in content and style as possible. Some space has also been given to the critical apparatus of the Japanese edition, i.e. comments, footnotes, afterwords etc., as well as to translations of the titles of individual parts of The song…